The causes and prevention of foul language in the youth environment (Actual Problems of Psychology in Educational Institutions, 2022)
The article presents the concept of faul language, its influence on the formation of the personality. The causes for using non-normative vocabulary are analyzed and preventive and corrective exercises are suggested. It is concluded that it is difficult to completely get rid of this phenomenon in society, but most people are aware of the problem of faul language, seriously thinking about their culture of behavior and trying to change.